Describing East Malaysian Tadpole Diversity : Status and Recommendations For Standards and Procedures Associated With Larval Amphibian Description and Documentation - Haas, A.; Das, I. (Bonner Zoologische Monographien, 2011)
Our ad hoc survey of 130 books and monographs showed that almost 70% did not present any descriptive information on larval anurans, and when larval stages were included the quality of documentation often tended to be poor. The larval (or developmental) stages of 51 species of east Malaysian frogs still remain unknown. Modern methods and techniques have changed the way we treat larvae taxonomically, and we recommend their adoption in tadpole research. Notably, DNA barcoding allows for unequivocal matching with adult frogs, and digital color photography provides documentation of tadpole features of unprecedented quality, partly replacing traditional drawings. Both techniques are considered essential for the study of tadpoles. Tadpole measurements have now reached a high level of standardization and can be performed quickly, accurately, and easily with digital microscopes. Nevertheless, line drawings and SEM may still be valuable techniques when certain details need to be demonstrated.